An Analytical Study of the Religious Thoughts of Allama Muhammad Iqbal in the Renaissance of the Muslims of Subcontinent - Aftab, Atif; M. Arsalan Shoeby, Syed; Ara, Anjum (Pakistan Social Sciences Review, 2022)
The deep-rooted concern of Islam is to develop the mankind to the total submission of his Lord. The purpose was enlightenment of human souls through divine guidance and carry out masses from the gloom and obscurity conditions. Islam flourishes from humble beginning to the civilization. After reaching its apex a continuous decline was observed in the name of modernity through amalgamation of different culture, norms and civilizations. Muslims world confronted lots of problem after the fall of its intellectual center at Baghdad in 1258. Muslims intellectuals, who made progressive work, gave creative ideas, great discoveries, new inventions and innovation which amazed the western world became deprived and experiencing miserable conditions. Same happened in the sub-continent where the Muslims lagged behind other communities. The decline of Muslim rulers increases the state of lethargy to its height. In such circumstances where the tension between the west and Islamization, Sub-continent produced one out standing figure, Sir Muhammad Iqbal, the most serious thinker and philosopher who maintained balance between the conservatives and modernization. Iqbal propagate the real essence of Islam that creates profound effects in the renaissance of Muslims and restoration of Islam. This research intends to recall the Iqbal views and his ideology which provides the remedy in the awful conditions of subcontinent.